PREPOSITIONS IN EU AND DOMESTIC JUDGMENTS – A CORPUS ANALYSIS OF THE DISTRIBUTION AND FUNCTIONS OF SIMPLE, COMPLEX AND SECONDARY PREPOSITIONS - KOŹBIAŁ, Dariusz (Comparative Legilinguistics, 2019)
The article aims to examine the distribution of simple, complex and secondary prepositions in EU judgments (based on a corpus of judgments of the Court of Justice and the General Court) and domestic judgments (based on a corpus of judgments of the Polish Supreme Court) against general Polish (based on a balanced version of the Polish National Corpus), and to analyze the functions of complex and secondary prepositions. The results confirmed the hypothesis that the high distribution of prepositions in judgments against a representative sample of general Polish is a generic feature of judgments. In addition, it was established that the phraseological profile of EU judgments differs from the profile of national judgments in terms of the distribution of prepositions and their specific functions. This may be the result of the impact of the translation process on target language texts and the scope of jurisdiction of the EU courts and the national court, both of which affect the subject matter of judgments.